2015
DOI: 10.1089/scd.2014.0415
|View full text |Cite
|
Sign up to set email alerts
|

Cell Polarity and Neurogenesis in Embryonic Stem Cell-Derived Neural Rosettes

Abstract: Embryonic stem cells (ESCs) undergoing neural differentiation form radial arrays of neural stem cells, termed neural rosettes. These structures manifest many of the properties associated with embryonic and adult neurogenesis, including cell polarization, interkinetic nuclear migration (INM), and a gradient of neuronal differentiation. We now identify novel rosette structural features that serve to localize key regulators of neurogenesis. Cells within neural rosettes have specialized basal as well as apical sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 77 publications
3
36
0
Order By: Relevance
“…Multicellular rosettes are one of the crucial shapes during morphogenesis in diverse organ systems and play an important role in brain development. It has been demonstrated that neural rosettes recapitulate the developmental steps of embryonic brains (Banda et al, 2015;Curchoe et al, 2012;Elkabetz et al, 2008;Grabiec et al, 2016;Hȓı́bkováet al, 2017;Pasça et al, 2015). The cytoarchitecture of neural rosettes provides regulatory microenvironments (or niches) to balance between NSC proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multicellular rosettes are one of the crucial shapes during morphogenesis in diverse organ systems and play an important role in brain development. It has been demonstrated that neural rosettes recapitulate the developmental steps of embryonic brains (Banda et al, 2015;Curchoe et al, 2012;Elkabetz et al, 2008;Grabiec et al, 2016;Hȓı́bkováet al, 2017;Pasça et al, 2015). The cytoarchitecture of neural rosettes provides regulatory microenvironments (or niches) to balance between NSC proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The central nervous system (CNS) develops initially from a monolayer of neuroepithelial (NE) cells, which then roll up to form the neural tube. Within the neural tube, neural stem cells (NSCs) organize to form rosette structures (called neural rosettes), which have been reported in vivo and in vitro (Banda et al, 2015;Colleoni et al, 2010;Curchoe et al, 2012;Elkabetz et al, 2008;Grabiec et al, 2016;Harding et al, 2014;Mirzadeh et al, 2008;Pasça et al, 2015). Pluripotent stem cell (PSC)-based in vitro systems recapitulate embryonic brain development in many aspects; for example, the temporal appearance and spatial locations of neural cells, and the microenvironment regulating NSCs (Falk et al, 2016;Lancaster et al, 2013;Shi et al, 2012;Ziv et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…In the mammalian brain for example, Notch receptor and a Notch cleaving protein, Presenilin1, are found overall apically and there is evidence that the Notch intracellular domain is cleaved at the apical surface of neural progenitors to be later translocated to the nuclei [32,63]. Delta antibody is also internalised at the apical surface of neuroepithelial cells [32], supporting the hypothesis that Delta-Notch interactions may take place at the apical surface at the adherens junctions.…”
Section: Where Do Delta-notch Interactions Occur?mentioning
confidence: 88%
“…These works suggest that, from the moment of division, neuronal daughter cells are initially primed to activate the Notch signalling pathway in their sister cells and later, during apical detachment, in the surrounding tissue. While the location and timing of Delta-Notch interactions are better defined in Drosophila systems [56,[67][68][69][70][71][72], less is known about the location and mechanisms of Delta-Notch interactions during neurogenesis and neuronal differentiation in the vertebrate neuroepithelium [32,54,63,66]. Delta is observed in basal protrusions [54] and at the apical surface [32], while Notch receptor is cleaved at the apical surface of neuroepithelial cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…hESC SFTA3 and NKX2.1 control and KO cell lines were maintained and passaged as previously described (25). Neural differentiation of ESCs was initiated using the ALK2/3 inhibitor LDN-193189 (Stemgent, 100 nM) and progenitors ventralized to an MGE-like identity by a combination of sonic hedgehog (R&D Systems, 125 ng/mL) and its agonist purmorphamine (Calbiochem, 1 µM) as previously described (26).…”
Section: Methodsmentioning
confidence: 99%